Phytochemical and Hypoglycemic Evaluation of Alangium Salviifolium Root Extract - A., Ahad H.; S, Padmaja B.; P, Yesupadam; P, Guruprakash; M, Sravanthi; P, Ramyasree (Journal of Scientific Research, 2011)
. The main purpose of present study was to perform phytochemical screening and explore the anti-hyperglycaemic properties of Alangium salvifolium root extract in normal and alloxan induced diabetic rats. A. salvifolium root gave maximum extractive values of 6.4 % w/w with Ethanol and other parameters were within limits. The extract gave positive tests for phytosterols, triterpenes, flavonoids, carbohydrates and alkaloids. The ethanolic extract of A. salvifolium was found to be nearly as potent as tolbutamide in decreasing the blood glucose levels in normal fasting rats. In normal control group the percent reduction in blood glucose indicated that the extract is fast acting. The extract showed significant decrease in blood glucose, when compared with tolbutamide. The evaluated blood glucose levels in alloxan induced diabetic rats were significantly decreased up to 24th h compared to tolbutamide. A single oral administration of alcoholic extract at doses 100, 250 and 500 mg per kg produced a significant blood glucose reduction in a dose dependent manner in normal and diabetic rats. These data confirm the hypoglycaemic and anti-hyperglycaemic effect of alcoholic extract of A. salvifolium root in normal and diabetic rats respectively when compared with standard drug tolbutamide. Keywords: Alangium salvifolium; Ethanolic extract; Alloxan induced; Hypoglycaemic action. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.7047 J. Sci. Res. 3 (2), 393-402 (2011)